NOMINA DALAM BAHASA INGGRIS DAN BAHASA TABARU - TEDUMINGGIR, KRISTIANTO DANIEL (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research is entitled ‘’Nomina dalam Bahasa Inggris dan Bahasa Tabaru (Suatu Analisis Kontrastif)’’. The objects of the research are to identify and classify the kinds and function of noun in English and Tabaru Language, The writer uses the concept by Thomson and Martinet (1986), and analyzed the data by using contrastive methods to find out the differences based on the theory of Lado (1971). The English data were collected from some English book. While the Tabaru Language data were collected from some informants. The result shows that there are differences between the function of nouns in English and Tabaru Language in terms of function on possesive case. The Possesive case form in English attach to the apostrophe‘s while the possessive case in Tabaru Language does not. Keywords: Nomina in English and Tabaru Language: Contrastive Analisis